The structure and the leadership: The actualization of good management of Indonesian University - Risanty Risanty; Sambas Ade Kesuma (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
The objective of this paper is to discuss the concept of good university governance and the structure of university in Indonesia. In particular, the paper focuses on the structure of university in order to improve the good university governance in Indonesia. Good University Governance is basically setting the organizational structure, the process of business, as well as program and activities in the planning procedure. Leaders are different from managers. The leader is chosen and earned the academic leadership and the authority. Academic leaders are mandated to lead and a combination of academic leaders and managers. A university should apply academic leadership in every level. It is necessary to implement the checks and balances of executive authority, which can be performed by the university and faculty academic senate. Avoid conflicts of interest as well as multiple positions in implementing good governance in a university.